The effects of foraminotomy and distraction-stabilization on the dimensions of the lumbosacral neuroforamen throughout range of motion - Raphael Arz; Brian Park; Sebastian Knell; Antonio Pozzi; Frank Steffen; Lucas A. Smolders (The Veterinary Journal, 2026)

The quagga mussel (Dreissena bugensis) south of the Alps: an ongoing biological invasion in Lake Garda - Francesca Ciutti; Luca Bonacina; Andrea Chemello; Adriano Boscaini; Fabio Buzzi; Silvia Costaraoss; Giorgio Franzini; Laura Fravezzi; Federica Giacomazzi; Giovanna Pellegrini; Sabrina Pozzi; Chiara Zampieri; et al. (Aquatic Ecology, 2025)
Over the past century, Lake Garda has been increasingly affected by the introduction of several non-indigenous species. In early 2022, the identification of Dreissena bugensis (quagga mussel) marked the first record of a naturalized population in lakes south of the Alps. To investigate the colonization patterns of this invader and its potential interaction with the established invader D. polymorpha (zebra mussel), a comprehensive field survey was conducted in 2022 across twelve stations, encompassing littoral, sublittoral, and profundal zones, during both spring and autumn. By spring 2022, quagga mussels had colonized the littoral and sublittoral zones of nearly all stations, with higher density in the northern part of the lake and a growth rate dependent on depth. Between spring and autumn, their population continued to grow, surpassing zebra mussels at all stations and expanding into the profundal zone as well. Analysis of population structure and veliger monitoring suggest that quagga mussels likely arrived in the lake in 2019. The evidence of D. bugensis already being firmly established in Lake Garda, as well as in nearby Lake Ledro, highlights the need for biosecurity protocols to prevent further invasions and the spread of established invaders to other Italian lakes.

A screening of metal(loid) content in conventional and compostable plastic polymers: understanding the sources and the connected environmental implications - Gilberto Binda; Stefano Carnati; Noemi Passignani; Rachel Hurley; Luca Nizzetto; Davide Spanu; Gabriela Kalčíková; Andrea Pozzi (Environmental Pollution, 2025)

Freeze or escape? Tadpoles' behavioural decisions based on conspecifics' chemical alarm cues - Lucas D. Jungblut; Araceli R. Coceres; Marilina Raices; Carola A.M. Yovanovich; Andrea G. Pozzi (Animal Behaviour, 2025)

Introduction to the Special Issue on What They Do in the Shadows: New Perspectives on Africa’s Nocturnal Bushbabies - Frank P. Cuozzo; Michelle L. Sauther; Luca Pozzi; John K. Dalton (International Journal of Primatology, 2024)

Overcoming Challenges to Extracting and Sequencing Historical DNA to Support Primate Evolutionary Research and Conservation, with an Application to Galagos - Anna Penna; Mary E. Blair; Hsiao-Lei Lui; Elsa Peters; Logan Kistler; Luca Pozzi (International Journal of Primatology, 2024)

Hidden in the Dark: A Review of Galagid Systematics and Phylogenetics - Anna Penna; Luca Pozzi (International Journal of Primatology, 2024)

Assessing Ecological Divergence and Speciation Scenarios of the Paragalago zanzibaricus Species Complex Through Climatic Niche Modeling - Evan Miller; Averee Luhrs; Amanda Mancini; Mary E. Blair; Luca Pozzi (International Journal of Primatology, 2024)

Towards harmonization of metal(loid)s determination in conventional and compostable plastics: Comparison of acid digestion protocols in LDPE and PBAT/TPS blends - Stefano Carnati; Andrea Pozzi; Davide Spanu; Roberta Bettinetti; Luca Nizzetto; Gabriela Kalčíková; Ludovica Botta; Gilberto Binda (Chemosphere, 2024)

Impact of Pressure Guidewire on Model-Based FFR Prediction - Alessia Lucca; Luigi Fraccarollo; Fredrik E. Fossan; Anders T. Bråten; Silvia Pozzi; Christian Vergara; Lucas O. Müller (Cardiovascular Engineering and Technology, 2024)
Introduction Fractional Flow Reserve (FFR) is used to characterize the functional significance of coronary artery stenoses. FFR is assessed under hyperemic conditions by invasive measurements of trans-stenotic pressure thanks to the insertion of a pressure guidewire across the coronary stenosis during catheterization. In order to overcome the potential risk related to the invasive procedure and to reduce the associated high costs, three-dimensional blood flow simulations that incorporate clinical imaging and patient-specific characteristics have been proposed. Purpose Most CCTA-derived FFR models neglect the potential influence of the guidewire on computed flow and pressure. Here we aim to quantify the impact of taking into account the presence of the guidewire in model-based FFR prediction. Methods We adopt a CCTA-derived FFR model and perform simulations with and without the guidewire for 18 patients with suspected stable CAD. Results Presented results show that the presence of the guidewire leads to a tendency to predict a lower FFR value. The FFR reduction is prominent in cases of severe stenoses, while the influence of the guidewire is less pronounced in cases of moderate stenoses. Conclusion From a clinical decision-making point of view, including of the pressure guidewire is potentially relevant only for intermediate stenosis cases.

Exposure to environmental pollutants and attention-deficit/hyperactivity disorder: an overview of systematic reviews and meta-analyses - Eleonora Rosi; Alessandro Crippa; Marco Pozzi; Stefano De Francesco; Mariachiara Fioravanti; Maddalena Mauri; Massimo Molteni; Luisa Morello; Luca Tosti; Francesca Metruccio; Emilio Clementi; Maria Nobile (Environmental Science and Pollution Research, 2023)
Although heritability estimates suggest a role for genetic components, environmental risk factors have been described as relevant in the etiology of attention deficit/hyperactivity disorder (ADHD). Several studies have investigated the role of toxicological pollution, i.e., air pollution, heavy metals, POPs, and phthalates. Clear evidence for association of ADHD and environmental factors has not been provided yet. To answer this, we have assessed all available systematic reviews and meta-analyses that focused on the association between pollutant exposure and either ADHD diagnosis or symptoms. More than 1800 studies were screened of which 14 found eligible. We found evidence of a significant role for some pollutants, in particular heavy metals and phthalates, in the increased risk of developing ADHD symptoms. However, at the current stage, data from existing literature also do not allow to weight the role of the different environmental pollutants. We also offer a critical examination of the reviews/meta-analyses and provide indications for future studies in this field. PROSPERO registration: CRD42022341496

Insights into the effect of polyethylene terephthalate (PET) microplastics on HER2 signaling pathways - Lishan Cui; Luca Digiacomo; Siyao Xiao; Junbiao Wang; Augusto Amici; Daniela Pozzi; Giulio Caracciolo; Cristina Marchini (Toxicology in Vitro, 2023)

Selection of the optimal extraction protocol to investigate the interaction between trace elements and environmental plastic - Gilberto Binda; Stefano Carnati; Davide Spanu; Arianna Bellasi; Rachel Hurley; Roberta Bettinetti; Damiano Monticelli; Andrea Pozzi; Luca Nizzetto (Journal of Hazardous Materials, 2023)

In Memory of Judith Masters and Fabien Génin - Curswan A. Andrews; Sébastien Couette; Massimiliano Delpero; Luca Pozzi; Trudy Turner (International Journal of Primatology, 2023)

Physicochemical and biological ageing processes of (micro)plastics in the environment: a multi-tiered study on polyethylene - Gilberto Binda; Giorgio Zanetti; Arianna Bellasi; Davide Spanu; Ginevra Boldrocchi; Roberta Bettinetti; Andrea Pozzi; Luca Nizzetto (Environmental Science and Pollution Research, 2023)
Pollution by plastic and microplastic impacts the environment globally. Knowledge on the ageing mechanisms of plastics in natural settings is needed to understand their environmental fate and their reactivity in the ecosystems. Accordingly, the study of ageing processes is gaining focus in the context of the environmental sciences. However, laboratory-based experimental research has typically assessed individual ageing processes, limiting environmental applicability. In this study, we propose a multi-tiered approach to study the environmental ageing of polyethylene plastic fragments focusing on the combined assessment of physical and biological processes in sequence. The ageing protocol included ultraviolet irradiation in air and in a range of water solutions, followed by a biofouling test. Changes in surface characteristics were assessed by Fourier transform infrared spectroscopy, scanning electron microscopy, and water contact angle. UV radiation both in air and water caused a significant increase in the density of oxidized groups (i.e., hydroxyl and carbonyl) on the plastic surface, whereby water solution chemistry influenced the process both by modulating surface oxidation and morphology. Biofouling, too, was a strong determinant of surface alterations, regardless of the prior irradiation treatments. All biofouled samples present (i) specific infrared bands of new surface functional groups (e.g., amides and polysaccharides), (ii) a further increase in hydroxyl and carbonyl groups, (iii) the diffuse presence of algal biofilm on the plastic surface, and (iv) a significant decrease in surface hydrophobicity. This suggests that biological-driven alterations are not affected by the level of physicochemical ageing and may represent, in real settings, the main driver of alteration of both weathered and pristine plastics. This work highlights the potentially pivotal role of biofouling as the main process of plastic ageing, providing useful technical insights for future experimental works. These results also confirm that a multi-tiered laboratory approach permits a realistic simulation of plastic environmental ageing in controlled conditions.

Olfactory subsystems in the peripheral olfactory organ of anuran amphibians - Lucas David Jungblut; John O. Reiss; Andrea G. Pozzi (Cell and Tissue Research, 2021)

The role of forest expansion and contraction in species diversification among galagos (Primates: Galagidae) - Luca Pozzi (Journal of Biogeography, 2016)
Aim Here, I investigate galagid diversification and current distribution in the context of major climatic and geological events in sub‐Saharan Africa. Given their widespread distribution and presence in a large range of diverse habitats, galagids represent an excellent group to investigate the role of forest contraction and expansion on biological diversification in sub‐Saharan Africa. Location Sub‐Saharan Africa (Afrotropical Region). Methods I assembled a supermatrix including 53 nuclear loci and three mitochondrial markers for 94% of the galagid species currently recognized. Bayesian and maximum likelihood methods were used to infer phylogenetic relationships and times of divergence within the family. Ancestral ranges were estimated using several methods, including ‘BioGeoBEARS’ and rasp . Results Phylogenetic analyses corroborated previous results regarding the evolutionary history of this family: (1) early origin of the family soon after the Eocene‐Oligocene boundary; (2) dwarf galagos ( Galagoides spp.) represent a polyphyletic group with two well‐defined clades, one in central‐west Africa and one in the east; and (3) divergences within galagids are relatively old with most genera already present by the Late Miocene. The biogeographical analysis indicates central African origins and subsequent expansion to the east in the Early‐Middle Miocene. An expansion to the northern and southern savannas occurred between the Late Pliocene and the Middle Pleistocene. Main conclusions The results of this study clarify several questions related to the evolutionary history of the Galagidae in the context of sub‐Saharan African biogeography. This study suggests that galagid evolution and diversification was affected by three major climatic episodes: (1) the global cooling and forest contraction in the Early Oligocene, (2) the forest expansion and the uplift of the African rifts in the Miocene and (3) the aridification and extension of open woodlands and savannas in the Late Miocene and Plio‐Pleistocene.

The Use (and Misuse) of Phylogenetic Trees in Comparative Behavioral Analyses - Luca Pozzi; Christina M. Bergey; Andrew S. Burrell (International Journal of Primatology, 2014)

A New Method for Genome-wide Marker Development and Genotyping Holds Great Promise for Molecular Primatology - Christina M. Bergey; Luca Pozzi; Todd R. Disotell; Andrew S. Burrell (International Journal of Primatology, 2013)

Multi-technique characterization of dyes in ancient Kaitag textiles from Caucasus - Federica Pozzi; Gianluca Poldi; Silvia Bruni; Eleonora De Luca; Vittoria Guglielmi (Archaeological and Anthropological Sciences, 2012)

Canarypox and fowlpox viruses as recombinant vaccine vectors: an ultrastructural comparative analysis - Sole Pacchioni; Luca Volonté; Carlo Zanotto; Eleana Pozzi; Carlo De Giuli Morghen; Antonia Radaelli (Archives of Virology, 2010)

Amphibian larvae and zinc sulphate: a suitable model to study the role of brain-derived neurotrophic factor (BDNF) in the neuronal turnover of the olfactory epithelium - Carola A. M. Yovanovich; Lucas D. Jungblut; Tamara Heer; Andrea G. Pozzi; Dante A. Paz (Cell and Tissue Research, 2009)